Kemahiran Rasm Mushaf ̔Uthmani Guru J-QAF Negeri Terengganu (Jurnal Pembangunan Sosial, 2010)
Mastery skills in rasm Mushaf ‘Uthmani is an obligation and need to be learned and practiced by every Muslim. The mastery of rasm Mushaf ‘Uthmani will strengthen one’s skill in the Quran recitation as well as enhance his confidence and belief in the contents of the revealed text. This paper aims to analyze skill level of rasm Mushaf ‘Uthmani amongst j-QAF teachers at the primary schools in the state of Terengganu. The research design is based on the qualitative approach involving document analysis, interviews, observation and reading test. Quantitative approach involves the collection of data from the survey involving 427 guru j-QAF teachers of 2006–2007 intakes from 210 schools. The variables considered in this study were age, gender, education level, field of study and interest. The finding of the study shows that the level of mastery skills in rasm Mushaf ‘Uthmani amongst guru j-QAF teachers is high. The variable of age and interest in j-QAF learning program becomes contributing factor that is significant with respondents’ skill in rasm Mushaf ‘Uthmani amongst guru j-QAF teachers.